A test of life history strategy theory as a predictor of criminal violence across 51 nations. (July 2016) - Minkov, Michael; Beaver, Kevin
Abstract: Proponents of life history strategy (LHS) theory propose that it is an explanation of intra-societal non-political violence, such as homicide and assault. Criminologists usually prefer a different explanation: variation in national violent crime rates is a function of differences in social–structural characteristics, such as absolute or relative poverty (socioeconomic inequality). We found that national homicide rates and prevalence of muggings and attacks on people define a strong single criminal violence factor at the national level. We tested the predictive properties of various plausible predictors of this factor and, separately, of national murder rates. Only the two LHS variables (paternal absenteeism and adolescent fertility) predict the complex factor independently, whereas socioeconomic inequality (Gini), IQ, GDP, infant mortality, and pathogen prevalence do not. National murder rates are predicted by the two LHS variables and inequality but not by any other variables. This supports LHS theory as an explanation of national differences in criminal violence. Highlights: Life history strategy (LHS) has been proposed as an explanation of criminal violence. National murder, mugging, and assault rates define a common factor. This factor is best explained by differences in adolescent fertility and parental absenteeism. Socioeconomic inequality does not explain this factor. Our findings support LHS theory as an explanation of criminal violence.